Pigmentary Skin Disorders (Updates in Clinical Dermatology,, 2018)
Diagnosis and management of pigmentary skin disorders has become an important area in dermatology as the demand for treatment of these conditions has increased exponentially, particularly with skin of color. However, coverage in standard texts regarding various pigmentary disorders is insufficient and the need for focused attention on new developments and latest research findings is growing. Pigmentary Skin Disorders is written and edited by international leaders in the field and chapters include a practical clinical classification of pigmentary disorders, recent advances in vitiligo, current views on melasma, postinflammatory hyperpigmentation, lasers in pigmentary disorders, and drug-induced pigmentation. This volume is part of Springer's Updates in Clinical Dermatology series which aims to promote the rapid and efficient transfer of medical research into clinical practice. Covering new developments and innovations in all fields of clinical dermatology, it provides the clinician with a review and summary of recent research and its implications for clinical practice. Each volume is focused on a clinically relevant topic and explains how research results impact diagnostics, treatment options and procedures, as well as patient management. The reader-friendly volumes are highly structured with core messages, summaries, tables, diagrams and illustrations and are written by internationally well-known experts in the field.